2021
DOI: 10.3390/cancers13184612
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Potentiates the Anticancer Effect of Everolimus on Cervical Cancer In Vitro and In Vivo

Abstract: Cervical cancer is globally the fourth most common cancer in women. Metformin is a widely used drug for the treatment of type II diabetes and has been shown to possess important anticancer properties in cervical cancer. Everolimus is an mTOR inhibitor and is widely used to treat NETs, RCC, TSC, and breast cancers. The present study investigated the anticancer effects of metformin and everolimus in cervical cancer, when used alone or in combination. CaSki and C33A human cervical cancer cells were treated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…In particular, some studies involving metformin in non-diabetic cancer patients have yielded promising results [34,35]. Although recent studies by our group and others have found that metformin has significant anti-cervical cancer activity, the mechanisms behind this effect remain elusive [36][37][38][39]. To investigate this, we first used the CCK-8 assay to identify whether metformin induced anti-proliferative activities in different cervical cancer cells.…”
Section: Ampk Activation Impedes Cervical Cancer Tumor Growth In Vitr...mentioning
confidence: 99%
“…In particular, some studies involving metformin in non-diabetic cancer patients have yielded promising results [34,35]. Although recent studies by our group and others have found that metformin has significant anti-cervical cancer activity, the mechanisms behind this effect remain elusive [36][37][38][39]. To investigate this, we first used the CCK-8 assay to identify whether metformin induced anti-proliferative activities in different cervical cancer cells.…”
Section: Ampk Activation Impedes Cervical Cancer Tumor Growth In Vitr...mentioning
confidence: 99%
“…RT is an accepted treatment for CC, while reoccurrence of CC has emerged after RT owing to low radiosensitivity [ 53 , 54 ]. Additionally, mTOR inhibitor RAD001 possesses an anticancer effect on CC [ 55 ]. PD-L1 expression has been documented in most cervical squamous cell cancers, indicating the potential effectiveness of anti-PD-1 therapies for CC [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin is a therapeutic drug used for type 2 diabetes (15). Studies have shown that metformin can reduce the risk of breast cancer (16), cervical cancer (17,18), prostate cancer (19), gastric cancer (20) and other types of cancer. Metformin promotes an anti-inflammatory effect on macrophages by suppressing fatty acid synthase-dependent palmitoylation of AKT (21).…”
Section: Introductionmentioning
confidence: 99%